Rapid two-stage Starnes approach in high-risk neonates with Ebstein anomaly. (27th May 2020) - Asou, Toshihide; Kawataki, Motoyoshi; Takeda, Yuko; Asai, Hidetsugu; Tachibana, Tsuyoshi; Toyoshima, Katsuaki; Kim, Ki-Sung; Ueda, Hideaki
Abstract: OBJECTIVES: The purpose of this study is to review the short- and long-term outcomes of high-risk neonates with Ebstein anomaly treated with a newly developed rapid 2-stage Starnes procedure, which is aimed at reducing the size of the enlarged right side of the heart. METHODS: Fifty-two foetuses with Ebstein anomaly were analysed in this study and divided into 2 groups. The control group comprised 25 foetuses, referred to us before 2008, and the study group was composed of 27 foetuses, referred to us after 2009. The right atrial area index was defined as high risk when it was >1.5. We applied our management approach to 6 high-risk neonates in the study group. This approach consisted of reducing the size of the right side of the heart through a 2-stage process: (i) right atrial plication without the use of a bypass and (ii) a Starnes procedure. Cox proportional hazards models were used to evaluate the effects of our management approach on the survival rates of the neonates. RESULTS: The mean follow-up period was 7.5 ± 3.3 years. All 6 high-risk neonates in the study group survived. The overall hazard ratio was 0.12 (95% confidence interval of 0.03–0.43) in the study group as compared with the control group ( P = 0.0007). A Fontan operation was completed in all but 1 case, with the remaining case awaiting a Fontan operation. CONCLUSIONS: We suggest that a rapid 2-stage Starnes approach can be effective in the treatment of high-risk neonates with Ebstein anomaly.